Mathematics as Determinant of Students’ HOTS Among HND Electrical and Electronic Engineering Students in Ghana - Oduro-Okyireh, Theodore; Mulyanti, Budi; Rohendi, Dedi; Acheampong, Kennedy; Oduro-Okyireh, George (Journal of Education Reseach and Evaluation, 2023)
One crucial component of education is developing higher-order thinking skills (HOTS). The aim of this study is to analyze mathematics as determinant of students’ HOTS among HND electrical and electronic engineering student in Ghana. The test format tool used had two indicators, critical and creative thinking, and the subjects for the research were 488 electrical and electronic engineering students from 4 randomly selected Technical Universities in Ghana. The Cronbach Alpha reliability test was performed, and the Pearson test was used to assess the validity of the MAT instrument. Data were processed and analysed using SPSS version 26.0 software. Multiple regression was used as the estimation technique, and the results show a positive high correlation between HOTS and probability (0.757), and positive moderate correlations for algebra (0.669), functions (0.633), trigonometry and complex numbers (0.604), and calculus and differential equations (0.572). These statistics suggest that the level of understanding of mathematics concepts, particularly probability, can determine HOTS. The study's implication is that engineering mathematics curriculum developers should stress the practical applications of mathematics, especially probability in everyday life and offer opportunities for students to use their mathematical knowledge to solve real-world problems in order to develop HOTS.